Da’wah Message of Religous Pantun in Malay Pantun Published by Balai Pustaka - Wachid Eko Purwanto; Yosi Wulandari (Fakultas Bahasa dan Seni UNP, 2023)
In the 1920s, pantun became part of Islamic religious education in the archipelago. The aim of this study is to describe Islamic religious education in Pantun Melayu published by Balai Pustaka. This research method is descriptive qualitative. The research object of interest in this research is Islamic religious education in Pantun Melayu. Data was collected using reading and note-taking techniques and analyzed using content analysis based on the Islamic religious education data group in Pantun Melayu. The results of this study show that Islamic religious education in Pantun Melayu includes monotheism education, sharia education, moral education and education through Islamic stories. The five types of education in this pantun can be used as a medium for da'wah to strengthen the delivery of the message of Islamic education.